Rishikesh Shaha: A Historical Perspective - Acharya, Jayaraj (Journal of Foreign Affairs, 2022)
We must reflect upon the historical background of Nepal’s foreign policy and diplomacy, particularly at the United Nations (UN), to properly understand RishikeshSahah (1925- 2002) as a diplomat and politician. Shaha’s main contribution of public interest is related mainly to his role as Nepal’s permanent representative at the United Nations. During the Rana period, Nepal had the policy of keeping the country isolated from the rest of the world for fear of meddling by the British. JangaBahadur, the first Rana Prime Minister, had himself led the troops to assist the British colonialists in India to quell the police munity of 1857 and firmly expressed his assurance that there was no need for them to enter Nepal for any reason as they could benefit from Nepal without the need to colonize the country. Both the Ranas and the British colonial rulers in India had a common interest in keeping Nepal isolated from others but in close contact with British India for their own reasons. It is said that Nepal lost a total of about 60,000 soldiers in World War I and II. But, even as a sovereign independent state, Nepal did not participate in the San Francisco conference in 1945 to draft the Charter of the United Nations although it could have legitimately participated and become one of the founding members of the world organization. It was a missed opportunity.